(3GdeYGedGJ GdeGdjI GdeYGUQI aj Gdabg GdESdGejs - (3eMeO YKeGf(B, (3THjQs ((3YeGf(B:s (3OGQ GdfaGFS(B,s, 2001)
(3efgLjI GdJYGed eY GdeYGedGJ GdeGdjI GdeYGUQI (B- (3MbjbI GdeYGedGJ GdeGdjI GdeYGUQI(B- (3NUGFU abg GdeYGedGJ aj GdESdGe (B-(3efgL GdESdGe aj eYGdLI GdbVGjG GdeSJLOI(B- (3efgL GdJUOj ddeYGedGJ GdeGdjI GdeYGUQI(B- (3GdMbhb GdeYfhjI hGdNdhGJ hfXGe GdJCejf(B- (3GdHOjd GdESdGej dTQcGJ GdJCejf GdJLGQjI(B- (3GdfbhO hGdChQGb GdeGdjI hGdJLGQjI(B- (3eYGedGJ GdeUGQa GdESdGejI(B- (3eYGedGJ GdeUGQa GdESdGejI aj fXQ GdTQjYI(B- (3JYGed GdeUGQa GdESdGejI eY ZjQgG ef GdHfhcs
Keywords: (3GdEbJUGO GdESdGejs; (3GdHfhc GdESdGejIs; (3GdeYGedGJs